PENGARUH INTELEGENSI DAN MINAT SISWA TERHADAP PUTUSAN PEMILIHAN JURUSAN - Anna Rufaidah (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: The purpose of this research is to know whether there are significant effects of intelligence and student interests toward the decision of the selection programs . The research was conducted at Class XI at High School around Depok City with total sample 60 students that randomly taken. The method used in the research was a survey. Data of Intelligence Data intelligence were acquired from document obtained through an IQ test, Students’ Interests, and the decision of the selection programs were acquired from the test. The data was analysed using descriptive statistical method, multiple correlation coefficient, determination coefficient, and multiple regression analysis. To test the statistics is used ttest and ftest . The result of data analyzes shown there are significant effects of intelligence and Students’ Interests towards the decision of the selection programs   Keywords: Intelligence, Interest of Student,Decision of Selection Programs